Sovereign Wealth Funds - An Overview and Indian Perspective - Bansal, Anand; Pasricha, J. S. (Indian Journal of Finance, 2009)
The emergence of special purpose investment vehicles created by governments, popularly called Sovereign Wealth Funds (SWFs) has been one of the most striking developments in international finance in the recent years. The SWFs have been growing rapidly both in terms of their size and number. The present growth in SWFs is largely fuelled by a large accumulation of foreign exchange reserves in developing countries. The accumulation of foreign exchange reserves is the result of boom in capital inflows because of huge exports and portfolio investments inflows by FIIs in developing economies. Considering the growing role of SWFs in international capital markets as a separate investor class, the present paper focus on the conceptual framework of SWFs and recent growth of SWFs. Paper also provide insights into the role of SWFs during the recent subprime crisis. Finally the paper discusses the position of India from both points of view i.e. whether India should float its own SWF to increase return on its assets and the India’s policy as recipient country, regarding the investments made by SWFs in Indian capital market.